Monitoring and characterization of field‐evolved resistance to diamide insecticides in Spodoptera litura collected from eastern China - Che, Wunan; Li, Yunyi; Zhang, Daofeng; Qu, Cheng; Luo, Chen; Wang, Ran (Journal of applied entomology (1986), 2024)
Spodoptera litura is a notoriously destructive pest, which infests horticultural plants and economically important crops worldwide. Several generations of diamide insecticides have been used to combat S. litura throughout the world, causing various levels of resistance to this class of insecticides among wild S. litura populations. In this work, we monitored resistance to five diamide insecticides among 10 S. litura populations sampled from eastern China in 2022. In comparison with Lab‐S the susceptible strain, five of the tested populations displayed high susceptibility to three of the five diamide insecticides (cyantraniliprole, broflanilide and tetraniliprole). In contrast, there was significant resistance to the other two tested diamide insecticides, flubendiamide and chlorantraniliprole, in seven of the field‐collected populations. The Shanghai (SH) population showed high resistance to chlorantraniliprole (77.0‐fold), flubendiamide (25.5‐fold) and cyantraniliprole (27.8‐fold), respectively, than the strain of Lab‐S. Results of synergism tests in the SH population revealed that diethyl maleate (DEM) and piperonyl butoxide (PBO) greatly inhibited chlorantraniliprole resistance. The progeny of reciprocal crosses between the Lab‐S and SH populations presented dominance degrees of F1 progenies, suggesting that the chlorantraniliprole resistance was autosomal and incompletely recessive in SH. Above results of the current work offer useful knowledge for future formulation of field pest management strategies, allowing farmers to delay the development of resistance to diamide insecticides and thus promote sustainable management of S. litura.